2013
DOI: 10.1590/s0102-86502013001000003
|View full text |Cite
|
Sign up to set email alerts
|

Does acute alcohol intoxication interfere with colonic anastomosis wound healing?: a rat model of nondestructive colon trauma

Abstract: PURPOSE:To evaluate the effects of acute alcohol intoxication on healing of colonic anastomosis. METHODS: Thirty-six rats were allocated into two groups. Animals in the alcohol (A) were given 2 mL of ethanol diluted in 0.9% saline solution to a concentration of 40% by gavage immediately before anesthesia, whereas control (C) animals received 2 mL of 0.9% saline solution via the same route. A colonic anastomosis was then performed in all animals. On postoperative days 1, 3, and 7, anastomotic breaking strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In the same study, low and moderate preoperative alcohol consumption did not seem to be associated with the occurrence of complications in the postoperative period 13 . However, an experimental study with rats showed that acute alcohol intoxication did not alter the healing of colonic anastomosis wounds, although it increased the death rate in the postoperative period 14 . From this finding, the authors plan to study the effect of alcohol on wound healing through animal experiments in order to clarify these results.…”
Section: Discussionmentioning
confidence: 98%
“…In the same study, low and moderate preoperative alcohol consumption did not seem to be associated with the occurrence of complications in the postoperative period 13 . However, an experimental study with rats showed that acute alcohol intoxication did not alter the healing of colonic anastomosis wounds, although it increased the death rate in the postoperative period 14 . From this finding, the authors plan to study the effect of alcohol on wound healing through animal experiments in order to clarify these results.…”
Section: Discussionmentioning
confidence: 98%